Influence of parental perception of child’s physical fitness on body image satisfaction in spanish preschool children - Rojo Ramos, Jorge.; Mendoza Muñoz, María.; Castillo Paredes, Antonio Jonathan.; Galán Arroyo, Carmen. (MDPI, 2023)
It is well known that poor physical fitness is an exponential risk factor in the increase in chronic diseases, not only physical but also psychological. Even in childhood, a critical period of development, the perception of physical fitness plays a fundamental role in the individual’s self-concept of body image. Aim: To find out how self-perceived physical fitness influences self-perceived body image in preschoolers. Methods: 475 preschool pupils were recruited in the schools of Extremadura (Spain). They were administered a sociodemographic questionnaire, the Preschool Physical Fitness Index (IFIS) and the Preschool Body Scale (PBS). Findings: Significant correlations (p < 0.05) were observed between body dissatisfaction and perceived physical fitness (IFIS), being higher in girls. In terms of variables, general fitness (<0.001), cardio-respiratory fitness (<0.001), muscular strength (<0.001), speed/agility (<0.001) and balance (<0.001) have a negative, medium and significant association with body dissatisfaction in girls; however, this association was lower in the case of boys. Conclusions: The influence of physical fitness had a clear impact on self-perceived body image. With better findings on self-perceived physical fitness variables (IFIS) there was less body dissatisfaction (PBS), especially in the female sex. The results also showed that parents who perceived their children to be in poorer physical condition had higher body dissatisfaction. Therefore, it would be interesting for the context involved, particularly parents, to implement strategies to improve positive body image through the promotion of physical education and physical fitness at an early age.
Keywords: Body dissatisfaction; Body image perception; Self-concept; Niños; Aptitudes físicas